2015
DOI: 10.1016/j.ejphar.2015.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan alone and in combination with valsartan prevents stroke in Dahl salt-sensitive rats

Abstract: The effects of levosimendan on cerebrovascular lesions and mortality were investigated in models of primary and secondary stroke. We aimed to determine whether the effects of levosimendan are comparable to and/or cumulative with those of valsartan, and to investigate whether levosimendan-induced vasodilation has a role in its effects on stroke. In a primary stroke Dahl/Rapp rat model, mortality rates were 70% and 5% for vehicle and levosimendan, respectively. Both stroke incidence (85% vs. 10%, P<0.001) and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Of further note in this context is recent work by Trinh-Duc et al [ 72 ] that elegantly supports the rationale of using levosimendan instead of dobutamine or phosphodiesterase-III inhibitors to treat TTS induced by a subarachnoid haemorrhage: saving the brain from disastrous vasospasms while protecting the heart from excessive catecholamines and promoting recovery of faster contractile function. This is a development of a concept introduced in previous publications [ 73 , 74 ] but is still at too early a stage of assessment to be commented on further in this review.…”
Section: Takotsubo Syndromementioning
confidence: 99%
“…Of further note in this context is recent work by Trinh-Duc et al [ 72 ] that elegantly supports the rationale of using levosimendan instead of dobutamine or phosphodiesterase-III inhibitors to treat TTS induced by a subarachnoid haemorrhage: saving the brain from disastrous vasospasms while protecting the heart from excessive catecholamines and promoting recovery of faster contractile function. This is a development of a concept introduced in previous publications [ 73 , 74 ] but is still at too early a stage of assessment to be commented on further in this review.…”
Section: Takotsubo Syndromementioning
confidence: 99%
“…There is also evidence indicating that the neuroprotective effect of levosimendan is associated with its action as a vasodilator. In 2015, Levijoki et al reported that orally administered levosimendan increased the blood volume of the cerebral vessels, reducing mortality and morbidity in rat models of primary and secondary stroke 65 . In 2015, Matti Kivikko et al reported a pilot study showing that low-dose oral administration of levosimendan increased cerebral blood flow velocities in patients with an earlier ischemic cerebrovascular event, supporting the vasodilatory effect in the brain circulation 66 .…”
Section: Discussionmentioning
confidence: 99%
“…There are also evidences indicating that the neurorotective effect of levosimendan is associated with its action as a vasodilator. In 2015, Levijoki et al reported that orally administered levosimendan increased blood volume of the cerebral vessels, reducing mortality and morbidity in rat models of primary and secondary stroke 53 . In 2015, Matti Kivikko et al reported a pilot study showing that low dose oral administration of levosimendan increased cerebral blood ow velocities in patients with an earlier ischemic cerebrovascular event, supporting the vasodilatory effect in the brain circulation 54 .…”
Section: Discussionmentioning
confidence: 99%